The mediating role of management control system in the relationship between corporate governance and the performance of bailed-out banks in Nigeria - Aliyu, Nuraddeen Shehu; Muhammad Jamil, Che Zuriana; Mohamed, Rapiah (Elsevier Ltd., 2014)
This paper proposes the mediating influence of management control systems using performance measurement as a proxy in the relationship between corporate governance and performance of banks in an era of post banking crisis that called for a bailout reform.Since the performance measurement information is used to influence the behaviour of organizational resources to implement organizational strategies, this study will test its ability to strengthen and facilitates boards’ functional effectiveness in ensuring sound banks’ performance after the bail-out reform using Otley 2009 performance measurement model.